Pengembangan Media Pembelajaran Permainan Ular Tangga Untuk Meningkatkan Motivasi Belajar Siswa dan Hasil Belajar IPS di Madrasah Ibtidaiyah - Amifatuz Zuhriyah (Program Studi PGMI STAI Daruttaqwa Gresik, 2020)
The teacher is the main axis of education to determine the progress of a country in the future in general, the teacher’s job is to provide insight or teach knowledge to students so that they have knowledge and skills in each subject area. In addition, teachers also have the responsibility of educating students to have good attitudes and behavior, whether in the school environment, at home or in the community environtment. The learning media for this game of snakes and ladders in social science learning or abbreviated as (IPS) in elementary schools / madrasah ibtidaiyah, this media is to increase student motivation and student learning outcomes. One of the problems of education is the lack of facilities and infrastructure so that a teacher is required to be as creative as possible in improving the quality of learning in class, such as developing learning media. One of them is learning media that is interesting and overcomes boredom. Of a student in learning activities, namely learning based on the game of snakes and ladders in social science learning.